Prevalence of Frailty in Ankylosing Spondylitis, Psoriatic Arthritis, and Rheumatoid Arthritis: Data from a National Claims Dataset. Issue 4 (5th January 2022) - Lieber, Sarah B.; Navarro‐Millán, Iris; Rajan, Mangala; Curtis, Jeffrey R.; Sattui, Sebastian E.; Lui, Geyanne; Schwartzman, Sergio; Mandl, Lisa A.
Abstract : Objective: Frailty is associated with disability and mortality independent of age. Although studies have evaluated frailty in rheumatoid arthritis (RA), information on the prevalence of frailty in ankylosing spondylitis (AS) and psoriatic arthritis (PsA) is limited. We aimed to determine the prevalence of frailty in AS and PsA and to evaluate whether characteristics known to be associated with frailty, including anxiety, differ among these three types of inflammatory arthritis. Methods: We performed a cross sectional study of Centers for Medicare & Medicaid Services (CMS) beneficiaries aged 65 years or older with AS, PsA, or RA enrolled in 2014. We operationalized frailty using a validated claims‐based frailty index. We also explored the prevalence of frailty among CMS beneficiaries younger than age 65 years with work disability, a younger population that also may be at risk of frailty. Results: The prevalence of frailty in beneficiaries aged 65 years or older with AS and PsA was 45.2% and 46.7%, respectively, significantly lower than in RA (65.9%, P <  0.05). The prevalence of frailty in beneficiaries less than 65 years old was much lower overall, though still highest in RA; 11.7%, 4.4%, and 7.0% in RA, AS, and PsA, respectively ( P <  0.05). Anxiety was significantly associated with frailty in subjects of all ages, particularly among those less than 65 years old ( P <  0.05). Conclusion: Almost half of beneficiaries with AS or PsA aged 65 years old or older were frail, higher than in younger disabled beneficiaries. Further studies are needed to understand the risks of developing frailty in these diseases. Frailty was associated with anxiety, particularly in the younger age groups.